Alteration of Oxidative Phosphorylation as a Possible Mechanism of the Antifungal Action of P-Coumaric Acid Against Botrytis Cinerea - Cotoras-Tadic, M; Mendoza-Espinola, L; Mendoza-Espinola, L (2017)
Sin Editorial Disponible